Control Of Various Types Of Traps Flies In Pasar Aur Duri Jambi City - Susy Ariyani; Krisdiyanta Krisdiyanta; Budi Setiawan; Ramly Tarigan (Syntax Corporation Indonesia, 2023)
The background of flies as a mechanical vector of flies can spread disease, through germs (seeds of disease) attached to the legs, feathers, wings, body of flies so that flies can be dangerous to humans. The purpose of this study was to determine the control of various types of fly traps in Pasar Aur Duri Jambi City. This research method is quasi-experimental with a post test only design with control group with a statistical test approach Anova.The location of the study was on the stalls of fish traders, vegetable traders, and chicken traders in Pasar Aur Duri Jambi City. There are three types of traps, namely fly trap blowers, fly traps, and glue traps. Repetition in the study 9 times. The results of the study The number of flies trapped with fly trap blowers as fly control in Lapak 1 (fish traders), Lapak 2 (chicken meat traders) and stall 3 (vegetable traders) Pasar Aur Duri Jambi City showed that in the 1st to 9th repeats, the average number of flies trapped to the fly trap blower was 6 flies with flies trapped in Chrysomia megachepala as many as 116 flies. While the number of flies in the fly trap trapped was 54 flies, the average fly was 2 flies, and for the fly glue trap showed as many as 121 flies with an average of 3 flies, the type of fly trapped was Chrysomia megachepala. The results of one way Anova analysis showed that there was a significant difference in the number of flies trapped between Fly trap blowers, Fly traps, and Glue flies with F = 71.86; p < 0.001. Post-hoc analysis with the LSD method also showed that the Fly trap blower (M = 6.00; SD = 0.866) had significantly more flies than fly traps (M = 2.00; SD = 0.50) and Glue flies (M = 4.44; SD = 0.73), p < 0.001. While glue flies have a significantly greater number of flies trapped than fly traps (p < 0.001). Conclusion: The highest number of flies with a total of 334 flies with the effectiveness of trapping tools is Fly trap blowers and the most common type of fly Chrysomia megacephala. Suggestions for fly control in Pasar Aur Duri Jambi City should be to increase the full power of the portable flytrap blower that is easy to carry and place anywhere